PEMETAAN TINGKAT KEPEKAAN LINGKUNGAN PESISIR DI KOTA SEMARANG - Wibowo, Mardi (Jurnal Hidrosfir Indonesia, 2009)
Coastal zone of Semarang area has big potencial in fishery, tourism, industrial and service activities. In development of Semarang s coastal zone, is met much of environmental problems such as abration, land subsidence, sedimentation, water and land pollution and seawater intrusion. On the other hand, this area has limited carrying capacity and very sensitive to oil spill pollution and sedimentation. Therefore it is need index environmental sensitivity assessment/mapping with Geographical Information System (GIS) technology in Semarang s coastal zone. For Semarang s coastal zone development plan, should be: western part of Semarang s coastal zone is developed as fishery cultivation; central part as industrial, residential area activity and eastern part as fishery activity with special treatment and protection.